MARIA® M5: A multicentre clinical study to evaluate the ability of the Micrima radio-wave radar breast imaging system (MARIA®) to detect lesions in the symptomatic breast. Issue 116 (July 2019) - Shere, Mike; Lyburn, Iain; Sidebottom, Richard; Massey, Helen; Gillett, Caroline; Jones, Lyn
Abstract: The MARIA ® breast imaging system is a clinical diagnostic tool that uses a hemispherical array of radiowave antennas to generate three-dimensional images of the internal breast. The system utilises the variance of dielectric contrast within the breast volume in order to identify areas of interest for further diagnostic investigation. This multicentre study of 225 patients was conducted at three trial sites and recruited women with both malignant and benign lesions. The MARIA ® images from the study were read by both clinicians who had access to the patient's clinical information, as well as by 'blind' reviewers who did not. Results from the study show an overall sensitivity of 76% for the system, which was similar across benign and malignant findings, and in denser breasts. The results from this study are outlined here and discussions on ongoing and future work with MARIA ® are deliberated.